Comparative study of hysteroscopy, hysterosalpingography and transvaginal sonography in evaluation of the female infertility - Vohra, Shivangani; Tyagi, Mamta; Gupta, Smriti; Khanuja, Esha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: One of the most important and underappreciated reproductive health problems in developing countries is that of infertility. Objective of this study was to evaluate HSC (hysteroscopy), HSG (hysterosalpingography) and ultrasonography in infertility. Methods: This study was conducted among 100 infertile patients over a period of two years. The patients were questioned for the detailed history including socioeconomic status, medical history and previous history of taking any medications and supplements. The recruited patients had to undergo. Results: Transvaginal sonography and clinical examination were done. Transvaginal sonography detected abnormality in 40% of women. 65 women had normal hysterosalpingography findings whereas the rest 35 women had abnormal hysterosalpingography findings. Thirty nine percent (39%) had normal hysteroscopic findings while sixty one percent (61%) had abnormal findings. The study depicts that hysteroscopy has sensitivity (95%) and negative predictive value NPV (92%) whereas that of TVS is 48.9% and 44.9% respectively. Hysterosalpingography has sensitivity 68.3% and NPV 40.3%. Specificity (100%) and positive predictive value PPV (100%) of all the three modalities are the same. Conclusions: The results of the present study showed that each modality provided useful information but no single modality provided complete information for evaluating infertile women. Thus, a combination of all three modalities- TVS (transvaginal sonography), HSG (hysterosalpingography) and hysteroscopy is necessary to evaluate infertile women.